Development of the Foot and Ankle Activity Level Scale (FAALS): A Clinical Tool for Orthopaedic Surgeons - Lauren M. Matheny PhD, MPH; Thomas O. Clanton MD; Jonathon D. Backus MD FAAOS; Norman Waldrop MD; Karen Briggs MPH, MBA; Marilee Horan MPH; Anastasia Robinson PT, DPT, OCS (Foot & Ankle Orthopaedics)
Category: Ankle; Sports Introduction/Purpose: Activity level is a benchmark to document patient recovery. Currently, there is a lack of instrumentation that measures activity level in the foot and ankle. AAOS has recommended first establishing normative values when developing a new instrument to serve as a reference group for physicians, improving the interpretation of scores. The purpose of this study was to develop a foot and ankle activity level scale (FAALS) instrument that will serve as an effective clinical tool for practitioners and determine normative values for the FAALS instrument to serve as a baseline reference group for physicians. Methods: This was a 4-phase study (n=605). Items for the new instrument were develop in Phase 1 by interviewing experts through a systematic Delphi consensus process (orthopaedic surgeons, orthopaedic researchers/statisticians, physical therapists). Data were aggregated to form an initial pool of 101 activity items. Experts assessed items on content appropriateness and item difficulty. Items were reviewed for clarity and readability. Cognitive interviews were performed with two people in the normal population for interpretation assessment. From this review process, 24 items were removed, leaving 77 items for the pilot analysis in Phase 2. After final item reduction, there were 22 items included for the final FAALS instrument. Scale sensitivity was assessed with a multiple linear regression analysis. Normative values were determined for the remaining 22 items. Results: There are 4 activity levels with a defined point range for each activity level. Level 1 (lowest): 0-24 points, Level 2: 25-44 points, Level 3: 45-68 points, Level 4 (highest): 69-88 points. Person reliability was .92 and item reliability was 1.00, demonstrating excellent reliability. Mean-square infit/outfit values were between 1.28 and 0.73 demonstrating excellent evidence of validity. The FAALS instrument was sensitive to groups with expected foot and ankle functional differences for previous ankle surgery, t (502)=-7.69, p<.001) and body mass index (BMI), t (502)=-3.41, p<.001. Mean FAALS for individuals with previous ankle surgery was 56.7 (Level 3), and for no previous ankle surgery was 68.5 (Level 4). Mean FAALS for individuals with normal BMI was 73.3 (Level 4), and for obese or overweight was 63.2 (Level 3). Conclusion: A new 22-item foot and ankle activity level scale with 4 activity levels called the FAALS was developed for practitioners to quickly assess activity level in patients. There was excellent evidence of psychometric properties for reliability and validity of FAALS scores. The FAALS instrument demonstrated sensitivity in its ability to measure activity level between groups with known functional differences, including previous ankle surgery status and BMI. Orthopaedic practitioners can feel confident in using FAALS to assess activity level. Testing FAALS in the normal population was the first step according to AAOS recommendations. Further research should assess FAALS in surgical populations.